The Heckscher-Ohlin-Samuelson model and the Cambridge capital controversies - Kazuhiro Kurose; Naoki Yoshihara (University of Massachusetts, Department of Economics, 2016)
This paper examines the validity of the factor price equalisation theorem (FPET) in relation to capital theory. Additionally, it presents a survey of the literature on Heckscher-Ohlin-Samuelson (HOS) models that treat capital as a primary factor, beginning with Samuelson (1953). Furthermore, this paper discusses the Cambridge capital controversy, which contends that marginal productivity theory does not hold when capital is assumed to be as a bundle of reproducible commodities instead of as a primary factor. Consequently, it is shown that under this assumption, the FPET does not hold, even when there is no reversal of capital intensity. This paper also demonstrates that the recent studies on the dynamic HOS trade theory generally ignore the difficulties posed by the capital controversies and are thereby able to conclude that the FPET holds even when capital is modelled as a reproducible factor. Our analysis suggests that there is a need for a basic theory of international trade that does not rely on factor price equalisation and a model that formulates capital as a bundle of reproducible commodities.
Keywords: B51; D33; F11; 330; factor price equalisation; capital as the bundle of reproducible commodities; reswitching of techniques; capital reversing